Validation of analog sensor measurements in hydrometeorological participatory monitoring in various tropical countries - Mitze, Fabian; Jacobs, Suzanne Robin; Breuer, Lutz; Zeballos, Jazmin Campos; Codalli, Fabia; Shagega, Frank Paul; Weeser, Björn (Frontiers in Earth Science, 2026)
As remote tropical mountain regions often lack open data and traditional methods of collecting hydrometeorological data are not always feasible, this study validates an alternative participatory monitoring approach for collecting hydrometeorological data in mountainous regions in Ecuador, Honduras and Tanzania. Volunteers used analog low-cost sensors to measure air temperature, relative humidity, rainfall and water level. The measurements were validated with photos taken alongside the measurements. Data from selected stations were additionally validated against automatic sensor data using different metrics, such as the mean absolute error (MAE). In addition, errors made by frequent and non-frequent participants were compared, assessing the performance of these two target groups. In the period between May 2023 and May 2025 a total of 2,982 observations were received, whereby the majority were submitted by frequent participants (84.4%). A comparison between frequent and non-frequent users showed that the former measured with higher accuracy. The comparison with automatic sensor data showed a correlation for all parameters ranging from 0.42 to 0.96. The best results in terms of accuracy were achieved for air temperature (MAE: 0.74 °C–1.65 °C) and water level (MAE: 0.04–0.08 m). On the other hand, a high deviation was found for relative humidity (MAE: 16.76%–31.69%). This deviation was corrected by applying linear regression, resulting in moderate deviation (MAE: 5.45%–9.50%). Rainfall had a MAE ranging from 2.55 to 3.10 mm. This was mainly attributed to the low measurement frequency and the limited capacity of the rain gauges. Overall, the study showed ambivalent results, where analog thermometers and water level gauges can be considered the most promising alternatives to automatic sensor measurements. However, the hygrometers only provided moderate measurement quality, while the rain gauges used were too small to cover all rainfall in the periods analyzed.